Pengaruh Pengembangan Karier Terhadap Kinerja Pegawai Dengan Kompetensi Sebagai Variabel Intervening - Musfiratun, Musfiratun; Gunarto, Muji; Geraldina, Ira (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study aimed to determine whether career development positively impacts employee performance, with competence as an intervening variable (Paser District Health Department case study). Quantitative techniques are used in this study. This cohort consisted solely of Pacer's District Health Department staff, with 203 staff members. The sampling technique was proportionally stratified random samples. The sample included 103 employees. The data collection method used is a questionnaire with a Likert scale of 1-5. The data analysis technique uses a partial least squares (PLS) approach using SmartPLS software. The results of this study show that career development has a positive and significant impact on employee performance and that career development has a positive and significant impact on competency. That competency has a positive and significant impact on employee performance. Giving and showing that career development has a positive and significant impact. Impact on employee performance positively and significantly impacts employee performance through ability as an intervening variable. Thus, we can see that employee career development, supported by the right competencies, can support the achievement of improved performance